Sibling correlation in risk attitudes: Evidence from Burkina Faso - Mohammad H. Sepahvand; Roujman Shahbazian (Uppsala University, Department of Economics, 2018)
This study uses sibling correlation to investigate the importance of parental and household characteristics on three different risk domains collected in a nationally representative survey from Burkina Faso. Sibling correlations are between 0.51 and 0.83. The correlations are higher in the general risk domain compared to risk taking in financial matters and traffic. Moreover, the sibling correlation is higher for the younger generation of siblings than the older generation, and for sisters than brothers. We also explore which factors drive these correlations; parents' risk attitudes help explain these correlations, whereas socioeconomic outcomes, family structure, parental health and residential zone have only a limited contribution. We also find that gender is important in explaining the variation in sibling correlations. Mother's have a stronger contribution on daughter's correlation than fathers, whereas fathers help to explain the son's correlation to a larger extent.
urn:nbn:se:uu:diva-346866
Keywords: D1; D81; J6; Z1; 330; risk attitudes; family background; sibling correlations; Burkina Faso